Keragaman Genetik 96 Aksesi Plasma Nutfah Padi Berdasarkan 30 Marka SSR Terpaut Gen Pengatur Waktu Pembungaan (HD Genes) - Utami, Dwinita Wikan; Sutoro, Sutoro; Hidayatun, Nurul; Risliawati, Andari; Hanarida, Ida (Jurnal AgroBiogen, 2011)
Genetic Diversity of 96 Accession of Rice GermplasmUsing 30 SSR Markers Linked to Heading Date Genes (HDGenes). Dwinita W. Utami, Sutoro, Nurul Hidayatun,Andari Risliawati, and Ida Hanarida. Rice with earlymaturity is one of an important genetic resources in ricegermplasm collection. Characterization and identification ofgenetic diversity is an important issue for plant variety protection.Molecular identification by microsatellite markersusing Genetic Analyzer enables resolve of this issue. Theobjective of this research is to identify the genetic diversity of96 rice accessions based on their specific DNA fingerprintusing microsatellite markers. A total of 96 accessions consistingof a diverse variety of maturity classification weregenotyped with 30 SSR markers linked to HD genes whichspread out in 12 chromosomes of rice geneome. The total297 alleles were detected indicated the level of markerinformativeness. RM5607 generated 7 allele with the sizerange from 103 to 197 and the highest PIC at 0.90. RM3571(linked to HD12 gene) has a significant value associated withvarieties which have early maturity trait. Clustering analysisshowed the cluster based on Sub Species genome backgroundand on early maturity trait.